Dual xanthan gum/poly(vinyl acetate) or alkyl‐functionalized poly(vinyl alcohol) films as models for advanced coatings. Issue 19 (6th May 2014) - Puga, Alberto V.; Garcia‐Valls, Ricard; Fernández‐Prieto, Susana; Smets, Johan; York, David
ABSTRACT Double‐layer films, prepared by casting films of xanthan gum (XG), and subsequently poly(vinyl acetate) (PVAc) onto the former, are reported. The resulting XG/PVAc films provide high protection as coatings to a bleaching agent, 6‐(phthalimido)peroxyhexanoic acid, in liquid detergents, due to the combined roles of the outer PVAc layer as water‐barrier and the inner XG layer as water‐sink. PVAc films cast from either homogeneous solutions in acetone or aqueous dispersions were used; the stabilities exerted by the former were markedly superior. For comparison, poly(vinyl alcohol) (PVA) was also used as outer wall material, resulting in much lower protection due to its hydrophilicity. Functionalization (silylation or acetalyzation) of PVA films is also suggested as a means to decrease the surface hydrophilicity of the material. The dual hydrophilic–hydrophobic films presented herein serve as models for advanced coatings in (micro)encapsulation processes, owing to the straightforward study of their morphology and transport phenomena. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40870.